Hydraulic Resistance and Macromolecular Structure of Aerobic and Anaerobic Mixed-Culture Extracellular Polymeric Substances Gel Layers: Opportunities and Challenges - Dinis Costa, Emanuel Fonseca; Gagliano, Maria Cristina; Kemperman, Antoine; Rijnaarts, Huub H. M.; Lammertink, Rob G. H.; Temmink, Hardy (Frontiers in Environmental Science, 2022)
Soluble Extracellular Polymeric Substances (sEPS) are a mixture of microbial soluble polymers produced during aerobic or anaerobic treatment of wastewater. Gel layers mainly consisting of sEPS are usually present in the fouling layers of membrane bioreactors (MBRs) and in the dynamic membranes (DMs) of dynamic membrane bioreactors (DMBRs), and their properties have not been thoroughly investigated over the years. In this study, sEPS fractions recovered from aerobic and anaerobic reactors were analyzed and tested to build-up EPS gel layers on a 0.2 µm pore size polycarbonate carrier. Dead-end filtration experiments showed that anaerobic sEPS layers, which have a low polysaccharide:protein (PS:PN) ratio, had a lower hydraulic resistance than the aerobic sEPS gel layers, which show a high PS:PN ratio. Optical Coherence Tomography (OCT) and Confocal Laser Scanning Microscopy (CLSM) analyses highlighted that both layers had similar thicknesses and 3D structural organizations. Fluorescent staining of organics and biovolume analysis revealed that the anaerobic sEPS (low PS:PN), the abundance of proteins appears to destabilize the polysaccharide network increasing the water permeability through the layer. Additionally, the polysaccharides present in the anaerobic sEPS were mainly of the α-linked type, contributing to a more open crosslinked network within the layer, resulting in the low filtration resistance measured. The filtration characteristics observed in this study for the sEPS layers from anaerobic mixed cultures are of interest for possible future application of those layers as dynamic membranes within anaerobic reactors.